2005
DOI: 10.1038/sj.onc.1208964
|View full text |Cite
|
Sign up to set email alerts
|

Activated type I TGFβ receptor kinase enhances the survival of mammary epithelial cells and accelerates tumor progression

Abstract: We have examined the effects of transforming growth factor-beta (TGFb) signaling on mammary epithelial cell survival. Transgenic mice expressing an active mutant of Alk5 in the mammary gland (MMTV-Alk5 T204D ) exhibited reduced apoptosis in terminal endbuds and during postlactational involution. Transgene-expressing mammary cells contained lower Smad2/3 and higher c-myc levels than controls, high ligand-independent phosphatidylinositol-3 kinase (PI3K) and Akt activities, and were insensitive to TGFb-mediated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 55 publications
4
94
0
Order By: Relevance
“…A possible mechanism whereby Ki-ras drives metastasis may be promotion of nuclear accumulation of Smad2 previously phosphorylated by ALK5-TD, as has been suggested earlier for squamous carcinoma cells (Oft et al, 2002). It is interesting to note that when expressed in normal mammary epithelial cells in vivo, ALK5-TD-expressing mice did not develop mammary tumors, whereas bigenic MMTV-ALK5-TD x-Neu mice developed tumors that were more metastatic than those derived from MMTVNeu mice, suggesting that mutant ALK5 kinase (enhanced TGF-b signaling) can provide epithelial cells with a 'gain-of-function' effect that synergizes with oncogene/ ras-induced transformation (Siegel et al, 2003;Muraoka-Cook et al, 2005b). The underlying mechanism of prometastatic function of TGF-b/ALK5/Smad may, besides enhanced survival (Muraoka-Cook et al, 2005b), affect homing of ALK5-TD-expressing cells to liver as has been suggested for metastases of Smad4-positive breast cancer cells to bone (Deckers et al, 2006;Kang, 2006).…”
Section: Tgf-b Receptor Type I In Tgf-b-induced Tumor Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible mechanism whereby Ki-ras drives metastasis may be promotion of nuclear accumulation of Smad2 previously phosphorylated by ALK5-TD, as has been suggested earlier for squamous carcinoma cells (Oft et al, 2002). It is interesting to note that when expressed in normal mammary epithelial cells in vivo, ALK5-TD-expressing mice did not develop mammary tumors, whereas bigenic MMTV-ALK5-TD x-Neu mice developed tumors that were more metastatic than those derived from MMTVNeu mice, suggesting that mutant ALK5 kinase (enhanced TGF-b signaling) can provide epithelial cells with a 'gain-of-function' effect that synergizes with oncogene/ ras-induced transformation (Siegel et al, 2003;Muraoka-Cook et al, 2005b). The underlying mechanism of prometastatic function of TGF-b/ALK5/Smad may, besides enhanced survival (Muraoka-Cook et al, 2005b), affect homing of ALK5-TD-expressing cells to liver as has been suggested for metastases of Smad4-positive breast cancer cells to bone (Deckers et al, 2006;Kang, 2006).…”
Section: Tgf-b Receptor Type I In Tgf-b-induced Tumor Suppressionmentioning
confidence: 99%
“…It is interesting to note that when expressed in normal mammary epithelial cells in vivo, ALK5-TD-expressing mice did not develop mammary tumors, whereas bigenic MMTV-ALK5-TD x-Neu mice developed tumors that were more metastatic than those derived from MMTVNeu mice, suggesting that mutant ALK5 kinase (enhanced TGF-b signaling) can provide epithelial cells with a 'gain-of-function' effect that synergizes with oncogene/ ras-induced transformation (Siegel et al, 2003;Muraoka-Cook et al, 2005b). The underlying mechanism of prometastatic function of TGF-b/ALK5/Smad may, besides enhanced survival (Muraoka-Cook et al, 2005b), affect homing of ALK5-TD-expressing cells to liver as has been suggested for metastases of Smad4-positive breast cancer cells to bone (Deckers et al, 2006;Kang, 2006). More specifically, activated Smad signaling may induce factors through which the tumor cells communicate with the microenvironment of the metastasis site (Deckers et al, 2006), a process which is needed for optimal tumor cell growth and metastasis.…”
Section: Tgf-b Receptor Type I In Tgf-b-induced Tumor Suppressionmentioning
confidence: 99%
“…Human mammary epithelial cells (MCF10A) and mouse mammary epithelial cells (NMuMG) were grown as previously described. (6) Human keratinocyte cells (HaCaT), mouse mammary tumor cells (4T1) and human hepatoma cells (HepG2) were grown as previously described. (9) SRB assay.…”
Section: Methodsmentioning
confidence: 99%
“…(5) Transforming growth factor-b has at least two roles during carcinogenesis, for although it was initially found to be a tumor-suppressing cytokine, it also acts as a mediator of metastasis to the lung. (6,7) During the initial stage of metastasis, cancer cells undergo epithelial-to-mesenchymal transition (EMT), which involves loss of epithelial cell polarity, acquisition of the mesenchymal phenotype, greater motility and invasiveness, and disruption of cell-to-cell adhesion. (8) The EMT is generally induced in epithelial cells by signals released from mesenchymal cells that compose the stroma of normal and neoplastic tissues.…”
mentioning
confidence: 99%
“…In addition, it is becoming clear that Neu/ErbB-2-induced signaling pathways can be influenced by other signaling pathways leading to breast tumorigenesis. One good example of this is the transforming growth factorb (TGFb) pathway that functions with Neu/ErbB-2 to promote the metastatic process (Yang et al, 2002;Muraoka et al, 2003;Siegel et al, 2003;Wang et al, 2005;Muraoka-Cook et al, 2006;Northey et al, 2008). However, it is not very clear how these two signaling pathways synergize to amplify the metastatic response.…”
Section: Introductionmentioning
confidence: 99%